Two New Species of Microbothrium (Monogenea: Microbothriidae) Parasitic on Japanese Squalids (Elasmobranchii: Squaliformes) - Masato Nitta; Shogo Ota (Species Diversity)
Microbothrium Olsson, 1869 (Monogenea: Monopisthocotylea) is the type genus of Microbothriidae and presently comprises three accepted species that parasitize squaliform sharks. More than seven decades have passed since the species affiliated with this genus was last reported. This study describes two new Microbothrium species that parasitize the body surfaces of squalid sharks in Kyushu, southern Japan, along with their molecular data. Microbothrium myzolepis n. sp. was recovered from Squalus mitsukurii Jordan and Snyder, 1903, collected off Kuchino-erabu Island in Kagoshima Prefecture. The new species is distinguished from its congeners by the vaginal pore opening on the left side of the body, presence of a slightly curved vagina, and 1–2 turns in the sclerotized tube associated with the penis. In addition, two individuals of Cirrhigaleus barbifer Tanaka, 1912 reared at the Oita Marine Palace Aquarium (Umitamago) were found to be infected with M. cirrhigalei n. sp. This newly described species can be readily differentiated from the other four Microbothrium species by the presence of a muscular vaginal pore, simple vagina, and three turns in the sclerotized tube associated with the penis. Furthermore, the phylogenetic analysis presented in this study supports the monophyly of the Microbothriidae. However, this analysis did not support the monophyly of each subfamily, suggesting that the subfamily classification may not accurately reflect evolutionary relationships. This study provides a taxonomic key for the identification of Microbothrium species.